ANTI-INTERLEUKIN-17 MONOCLONAL ANTIBODY FOR THE TREATMENT OF ANKYLOSING SPONDYLITIS: RESULTS OF ANALYSIS OF A RUSSIAN PATIENT GROUP FROM THE RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED MEASURE 1 AND MEASURE 2 TRIALS - Sh. F. Erdes; L. N. Denisov; A. L. Maslyansky; O. B. Ershova; M. L. Stanislav; T. S. Salnikova; N. V. Izmozherova; O. M. Lesnyak (Научно-практическая ревматология, 2017)
The article summarizes the data of two randomized controlled trials (RCTs) Phase III MEASURE 1 and MEASURE 2 investigating the efficacy and safety of secukinumab (SEC) in treating ankylosing spondylitis (AS) and compares the data with the results obtained from Russian patients with active AS, who were enrolled in these RCTs.Subjects and methods. Among 590 patients included in the MEASURE 1 and MEASURE 2 trials, the Russian group totaled 107 patients: 44 and 29 patients took SEC in the MEASURE 1 and MEASURE 2 trials, respectively; 34 patients had placebo in the two trials.Results and discussion. A retrospective analysis of the results for the Russian patient group showed that the efficacy of SEC in treating AS was fully similar to that demonstrated in the entire MEASURE 1 and MEASURE 2 group cohort. At 1 to 16 weeks of SEC therapy, the MEASURE 1 trial Russian patients displayed a rapid clinical improvement in 52.6% (p = 0.043); and in the SEC 150- and 75-mg groups, ASAS20 improvement was achieved by 64% (p = 0.0015), respectively. The SEC 150-mg group in the MEASURE 2 trial exhibited an ASAS20 response in 66.7% of cases (p = 0.0063). The clinical response at 16 weeks in the patients randomized at baseline into SEC treatment groups was sustained for 52 weeks. The proportion of patients achieving ASAS20 response at 52 weeks was 63.2 and 68% in the MEASURE 1 trial (in the SEC 150- and 75-mg groups, respectively) and 73.3% in the MEASURE 2 trial (the SEC 150-mg group). At 52 weeks, ASAS40 reponse was achieved by 52.6% of the patients in the MEASURE 1 trial and by 60% of those in the MEASURE 2 trial (the SEC 150-mg group). In the MEASURE 1 trial, ASAS 5/6 response rates at 16 weeks were 42.1 and 52.0% in the SEC 150- and 75-mg groups (p = 0.0249 and p = 0.0013, respectively). In the MEASURE 2 trial, the proportion of the SEC 150-mg group patients achieving ASAS 5/6 response was 53.3% (p=0.0135). After 52 weeks, these rates were 57.9, 52, and 73.3%, respectively. The adverse reactions observed in both the placebo-controlled and later follow-up periods and in the Russian patient cohort suggest that SEC has an acceptable safety profile and good tolerability in patients with AC.